Experimental infection of chickens by a flagellated motile strain of Salmonella enterica serovar Gallinarum biovar Gallinarum - Lopes, P. D. [UNESP] (2016)
Salmonella enterica subsp. enterica serovar Gallinarum biovar Gallinarum (SG) causes fowl typhoid (FT), a septicaemic disease which can result in high mortality in poultry flocks. The absence of flagella in SG is thought to favour systemic invasion, since bacterial recognition via Toll-like receptor (TLR)-5 does not take place during the early stages of FT. In the present study, chicks susceptible to FT were inoculated with a wild type SG (SG) or its flagellated motile derivative (SG Flat). In experiment 1, mortality and clinical signs were assessed, whereas in experiment 2, gross pathology, histopathology, systemic invasion and immune responses were evaluated. SG Fla(+) infection resulted in later development of clinical signs, lower mortality, lower bacterial numbers in the liver and spleen, and less severe pathological changes compared to SG. The CD8(+) T lymphocyte population was higher in the livers of chicks infected with SG at 4 days post-inoculation (dpi). Chicks infected with SG had increased expression of interleukin (IL)-6 mRNA in the caecal tonsil at 1 dpi and increased expression of IL-18 mRNA in the spleen at 4 dpi. In contrast, the CD4(+)T lymphocyte population was higher at 6 dpi in the livers of birds infected with SG Fla(+). Therefore, flagella appeared to modulate the chicken immune response towards a CD4(+) T profile, resulting in more efficient bacterial clearance from systemic sites and milder infection. (C) 2016 Elsevier Ltd. All rights reserved.